2019
DOI: 10.1111/dme.14152
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography and ulcer prevention in the high‐risk diabetic foot: data from a single‐blind multicentre controlled clinical trial

Abstract: Aim To assess the usefulness of monthly thermography and standard foot care to reduce diabetic foot ulcer recurrence. Methods People with diabetes (n = 110), neuropathy and history of ≥ 1 foot ulcer participated in a single‐blind multicentre clinical trial. Feet were imaged with a novel thermal imaging device (Diabetic Foot Ulcer Prevention System). Participants were randomized to intervention (active thermography + standard foot care) or control (blinded thermography + standard foot care) and were followed up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…A larger randomised trial involving 304 participants is currently examining the cost-effectiveness and cost-utility of home foot temperature monitoring [9]. Recently, a further clinical trial reported on the efficacy of foot temperature monitoring performed at only monthly intervals at an out-patient clinic, rather than at home [24]. A thermal camera was employed to identify "hot spots" in order to advise on interventions, such as reductions in physical activity and improved offloading of the concerned area [24].…”
Section: Monitoring Foot Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…A larger randomised trial involving 304 participants is currently examining the cost-effectiveness and cost-utility of home foot temperature monitoring [9]. Recently, a further clinical trial reported on the efficacy of foot temperature monitoring performed at only monthly intervals at an out-patient clinic, rather than at home [24]. A thermal camera was employed to identify "hot spots" in order to advise on interventions, such as reductions in physical activity and improved offloading of the concerned area [24].…”
Section: Monitoring Foot Temperaturementioning
confidence: 99%
“…Recently, a further clinical trial reported on the efficacy of foot temperature monitoring performed at only monthly intervals at an out-patient clinic, rather than at home [24]. A thermal camera was employed to identify "hot spots" in order to advise on interventions, such as reductions in physical activity and improved offloading of the concerned area [24]. The trial included 110 people with a past history of a diabetes-related foot ulcers and reported no benefit of the intervention in preventing foot ulcers or improving health-related quality of life [24].…”
Section: Monitoring Foot Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been suggested that thermal asymmetry monitoring has no additional value for assessing the severity of diabetic foot infections [15]. Moreover, for patients at a high risk of developing foot ulcers, monthly intervention by thermography did not result in a significant reduction in ulcer recurrence rate or increased ulcer-free survival [19]. On a side note, in certain cases, foot temperature asymmetry requires the exclusion of patients with partial amputations or deformities [7].…”
Section: Introductionmentioning
confidence: 99%